Electrolyte, electrochemical device and electronic device

By using electrolyte containing lithium difluorosulfonimide, sulfur-containing compounds and propionate in lithium-ion batteries, the problem of damage to the electrochemical interface mask of lithium-ion batteries at high temperatures is solved, and better anti-fall performance and intermittent circulation performance are achieved.

CN119725725APending Publication Date: 2025-03-28NINGDE AMPEREX TECHNOLOGY LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510179047.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Lithium-ion batteries produce gas at high temperatures, resulting in damage to the electrochemical interface film on the surface of the positive electrode sheet, affecting its anti-fall performance and intermittent circulation performance.

Method used

An electrolyte is used that contains lithium difluorosulfonimide, sulfur-containing compounds and propionate. By regulating the proportion of these components, a structure with a high HOMO orbital energy level is formed, thereby improving the stability and uniformity of the electrochemical interface film.

Benefits of technology

During the charging and discharging process of lithium-ion batteries, the electrolyte forms a uniform and stable electrochemical interface mask, which reduces the formation of interface acid gas, improves the chemical properties and structural stability of the positive electrode active material, and thus improves the anti-fall performance and batch circulation performance of the electrochemical device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005276416310000221
    Figure BDA0005276416310000221
  • Figure BDA0005276416310000231
    Figure BDA0005276416310000231
  • Figure BDA0005276416310000251
    Figure BDA0005276416310000251
Patent Text Reader

Abstract

The invention provides an electrolyte, an electrochemical device and an electronic device, the electrolyte comprises lithium bis (fluorosulfonyl) imide, a sulfur-containing compound and propyl propionate, based on the mass of the electrolyte, the mass percentage content of the lithium bis (fluorosulfonyl) imide is A%, the mass percentage content of the sulfur-containing compound is B%, the mass percentage content of the propyl propionate is D%, B / A is greater than or equal to 0.3 and less than or equal to 4, and D is greater than or equal to 30 and less than or equal to 40. Through the arrangement, the risk that the alternating current impedance of the electrochemical device is increased under high voltage is reduced, and the anti-falling performance and intermittent cycle performance of the electrochemical device are improved.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This invention is a divisional application with application number 202411677261.7, application date November 22, 2024, and invention name “An electrolyte, an electrochemical device and an electronic device”. Technical Field

[0002] The present application relates to the field of electrochemical technology, and in particular to an electrolyte, an electrochemical device and an electronic device. Background Art

[0003] Electrochemical devices (such as lithium-ion batteries) are widely used in smart phones, wearable devices, consumer drones, electric vehicles and other fields due to their high energy density, long cycle life and no memory effect. With the widespread application of lithium-ion batteries in the above fields, the market has higher and higher requirements for the safety and cycle performance of lithium-ion batteries.

[0004] During the cycle process, lithium-ion batteries produce gas at high temperatures (>130°C), and the electrochemical interface (CEI) film on the surface of the positive electrode is easily damaged, which affects the drop protection performance and intermittent cycle performance of the lithium-ion battery. Summary of the invention

[0005] The purpose of the present application is to provide an electrolyte, an electrochemical device and an electronic device to reduce the AC impedance of the electrochemical device under high voltage and improve the anti-drop performance and intermittent cycle performance of the electrochemical device.

[0006] It should be noted that in the invention content of this application, lithium-ion batteries are used as an example of electrochemical devices to explain this application, but the electrochemical devices of this application are not limited to lithium-ion batteries. The specific technical solutions are as follows:

[0007] A first aspect of the present application provides an electrolyte comprising lithium bis(fluorosulfonyl)imide, a sulfur-containing compound and propyl propionate, wherein the mass percentage of the lithium bis(fluorosulfonyl)imide is A%, the mass percentage of the sulfur-containing compound is B%, and 0.3≤B / A≤4; preferably, 2≤B / A≤3.5; further preferably, 2.5≤B / A≤3; and the mass percentage of propyl propionate is D%, and 30≤D≤40, based on the mass of the electrolyte. When the electrolyte includes lithium bis(fluorosulfonyl)imide and a sulfur-containing compound and satisfies the value of B / A within the scope of the present application, during the charge and discharge process of the electrochemical device, especially during the first few charge and discharge processes, the bis(fluorosulfonyl)imide anions (FSI-anions) and sulfur-oxygen double bonds in the electrolyte can form a structure having the highest occupied molecular orbital (high HOMO orbital energy level) in the molecule, so the structure has stronger reducibility, and during the charge and discharge process of the electrochemical device, a uniform and stable electrochemical interface (CEI) film can be formed on the surface of the positive electrode sheet, and the structure can reduce the formation of interfacial acidic gases, and can reduce the risk of acidic gas corrosion of the positive electrode active material, thereby improving the chemical properties and structural stability of the positive electrode active material, thereby improving the anti-drop performance of the electrochemical device, effectively reducing the risk of increased AC impedance of the electrochemical device under high voltage, and improving the intermittent cycle performance of the electrochemical device. By selecting an electrolyte including propyl propionate and regulating the value of D within the above range, the risk of increased AC impedance value of the electrochemical device under high voltage conditions can be effectively reduced, and propyl propionate is conducive to a more uniform distribution of FSI- anions, and a more uniform LiF-containing CEI film can be formed at the interface between the positive electrode plate and the electrolyte, thereby improving the anti-drop performance and intermittent cycle performance of the electrochemical device.

[0008] In some embodiments of the present application, 0.2≤A≤1.5. In some embodiments of the present application, 0.5≤B≤4. In some embodiments of the present application, 0.2≤A≤1.5, and, 0.5≤B≤4. By regulating the value of A and / or B within the above range, the viscosity of the electrolyte is moderate, which is conducive to forming a stable and uniform CEI film during the charge and discharge process, reducing the AC impedance of the electrochemical device under high voltage, and improving the anti-drop performance and intermittent cycle performance of the electrochemical device.

[0009] By selecting an electrolyte including propyl propionate and regulating the value of D within the above range, the risk of increased AC impedance value of the electrochemical device under high voltage conditions can be effectively reduced, and propyl propionate is conducive to a more uniform distribution of FSI- anions, and a more uniform LiF-containing CEI film can be formed at the interface between the positive electrode plate and the electrolyte, thereby improving the anti-drop performance and intermittent cycle performance of the electrochemical device.

[0010] In some embodiments of the present application, 30.5≤A+D≤41. By regulating the value of A+D within the above range, lithium bis(fluorosulfonyl)imide and propyl propionate act synergistically, and propyl propionate can make the distribution of FSI- anions more uniform, which is conducive to forming a more uniform LiF-containing CEI film at the interface between the positive electrode plate and the electrolyte, thereby improving the anti-drop performance of the electrochemical device, and can effectively reduce the risk of increased AC impedance value of the electrochemical device under high voltage conditions, thereby improving the anti-drop performance and intermittent cycle performance of the electrochemical device.

[0011] In some embodiments of the present application, the sulfur-containing compounds include 1,3-propane sultone, 1-fluoro-1,3-propane sultone, 2-fluoro-1,3-propane sultone, 3-fluoro-1,3-propane sultone, 1-methyl-1,3-propane sultone, 2-methyl-1,3-propane sultone, 3-methyl-1,3-propane sultone, 1-propylene-1,3-sultone, 2-propylene-1,3-sultone, 1-fluoro-1-propylene-1,3-sultone, 2-fluoro-1-propylene-1,3-sultone, 3-fluoro-1-propylene-1,3-sultone, 1-fluoro-2-propylene-1 ,3-sultone, 2-fluoro-2-propylene-1,3-sultone, 1-methyl-1-propylene-1,3-sultone, 2-methyl-1-propylene-1,3-sultone, 3-methyl-1-propylene-1,3-sultone, 1-methyl-2-propylene-1,3-sultone, 2-methyl-2-propylene-1,3-sultone, 3-methyl-2-propylene-1,3-sultone, 1,4-butane sultone, 1,5-pentane sultone, methylene disulfonate, ethylene disulfonate, cyclopentane, methyl cyclopentane, 4,5-dimethyl cyclopentane or cyclobutene sulfone. In some embodiments of the present application, the sulfur-containing compound includes at least one of 1,3-propane sultone or cyclopentane sulfone. By selecting sulfur-containing compounds within the above-mentioned range, the structural stability of the interface between the positive electrode and the electrolyte can be improved, and the generated lithium-containing reduction product can be uniformly deposited on the negative electrode, thereby improving the intermittent cycle performance of the electrochemical device. It also effectively improves the pass rate of the drop test of the electrochemical device, thereby improving the anti-drop performance of the electrochemical device.

[0012] In some embodiments of the present application, the electrolyte further includes 3-bromo-5-chloro-1-phenylthiophene, and the mass percentage of 3-bromo-5-chloro-1-phenylthiophene is C%, 1.8≤C≤3.8 based on the mass of the electrolyte. By selecting an electrolyte including 3-bromo-5-chloro-1-phenylthiophene and regulating the value of C within the above range, it is beneficial to further form a uniform and stable solid electrolyte interface (SEI) film structure, improve the anti-drop performance of the electrochemical device; at the same time, reduce the generation of gas in the electrochemical device during the heating process, and improve the intermittent cycle performance of the electrochemical device.

[0013] In some embodiments of the present application, 2≤A+C≤4.8. By regulating the value of A+C within the above range, it is beneficial to further form a uniform and stable CEI film and SEI film, improving the anti-drop performance of the electrochemical device; at the same time, the generation of gas in the electrochemical device during the heating process is reduced, further improving the intermittent cycle performance of the electrochemical device.

[0014] The second aspect of the present application provides an electrochemical device, which includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte in any of the above embodiments. Therefore, the electrochemical device of the present application has low AC impedance under high voltage and has good anti-drop performance and intermittent cycle performance.

[0015] In some embodiments of the present application, the positive electrode plate includes a positive electrode material layer, the positive electrode material layer includes amorphous carbon; a ball with a diameter of 15 mm and a weight of 12 g falls on the positive electrode material layer from a height of 0.1 m to 0.5 m, and the thickness change rate of the positive electrode material layer is 1% to 20%. When the positive electrode plate meets the above conditions, the positive electrode plate has good conductivity, and the positive electrode plate has mechanical strength and hardness adapted to the electrolyte of the present application, and the positive electrode plate and the electrolyte work synergistically, which can effectively improve the high temperature puncture resistance, low temperature cycle performance and high temperature cycle performance of the electrochemical device, reduce the risk of increased AC impedance of the electrochemical device under high voltage, and improve the intermittent cycle performance of the electrochemical device and the anti-drop performance of the electrochemical device.

[0016] In some embodiments of the present application, the positive electrode material layer includes a first compound, the first compound includes at least one of polybutyl acrylate, polyethyl acrylate, polybutyl methacrylate or polymethyl methacrylate, and the mass percentage of the first compound is 0.01% to 0.28% based on the mass of the positive electrode material layer. By selecting the above-mentioned first compound and regulating the mass percentage of the first compound within the above-mentioned range, the positive electrode plate has good wetting properties adapted to the electrolyte of the present application, and the positive electrode plate and the electrolyte work synergistically to effectively improve the high-temperature anti-puncture performance, low-temperature cycle performance and high-temperature cycle performance of the electrochemical device, reduce the risk of increased AC impedance of the electrochemical device under high voltage, improve the intermittent cycle performance of the electrochemical device, and take into account the anti-drop performance of the electrochemical device.

[0017] In some embodiments of the present application, the thermal shrinkage rate of the separator in the width direction after the separator is unfolded at 160°C is F%, the thickness of the positive electrode sheet is Tμm, and 0.04≤F / T≤0.1. By regulating the value of F / T within the above range, the separator and the positive electrode sheet work synergistically, and the electrochemical device has better high-temperature cycle performance and structural stability, and also has better high-temperature puncture resistance.

[0018] The third aspect of the present application provides an electronic device, which includes the electrochemical device in any of the above embodiments. Therefore, the electronic device of the present application has good performance.

[0019] Beneficial effects of this application:

[0020] The present application provides an electrolyte, an electrochemical device and an electronic device. The electrolyte includes lithium bis(fluorosulfonyl)imide, a sulfur-containing compound and propyl propionate. Based on the mass of the electrolyte, the mass percentage of lithium bis(fluorosulfonyl)imide is A%, the mass percentage of the sulfur-containing compound is B%, and the mass percentage of propyl propionate is D%, 0.3≤B / A≤4, 30≤D≤40. Through the above arrangement, during the charge and discharge process of the electrochemical device, especially during the first few charge and discharge processes, the bis(fluorosulfonyl)imide anions and sulfur-oxygen double bonds in the electrolyte can form a structure with a high HOMO orbital energy level, so the structure has stronger reducibility. During the charge and discharge process of the electrochemical device, a uniform and stable CEI film can be formed on the surface of the positive electrode plate, and the structure can reduce the formation of interfacial acidic gases, and can reduce the risk of acidic gases corroding the positive electrode active material. Propionate is conducive to a more uniform distribution of FSI- anions, and a more uniform LiF-containing CEI film can be formed at the interface between the positive electrode plate and the electrolyte, thereby improving the chemical properties and structural stability of the positive electrode active material, thereby improving the anti-drop performance of the electrochemical device, effectively reducing the risk of increased AC impedance of the electrochemical device under high voltage, and improving the intermittent cycle performance of the electrochemical device.

[0021] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.

[0023] It should be noted that in the specific implementation of the present application, lithium-ion batteries are used as an example of electrochemical devices to explain the present application, but the electrochemical devices of the present application are not limited to lithium-ion batteries. The specific technical solution is as follows:

[0024] The first aspect of the present application provides an electrolyte, which includes lithium bis(fluorosulfonyl)imide (LiFSI) and a sulfur-containing compound. Based on the mass of the electrolyte, the mass percentage of lithium bis(fluorosulfonyl)imide is A%, the mass percentage of the sulfur-containing compound is B%, and 0.3≤B / A≤4. For example, the value of B / A can be 0.3, 0.5, 0.8, 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5, 3.8, 4 or a range consisting of any two of the values. When the value of B / A is too large (greater than the upper limit of the present application), the viscosity of the electrolyte is large, which is not conducive to the thickness uniformity of the CEI film at the interface between the positive electrode sheet and the electrolyte. The uneven thickness of the CEI film leads to different electrolyte circulation speeds, which increases the side reactions in the local area and brings about an increase in the byproducts of the reaction between the electrolyte and part of the positive electrode active material, thereby affecting the anti-drop performance and intermittent cycle performance of the electrochemical device. When the value of B / A is too small (lower than the lower limit of the present application), the stability of the CEI film formed during the charge and discharge process is poor, and it is difficult to form a relatively uniform CEI film, resulting in expansion of the electrochemical device and increased gas production. When the electrolyte includes lithium bis(fluorosulfonyl)imide and a sulfur-containing compound and satisfies the value of B / A within the scope of the present application, during the charge and discharge process of the electrochemical device, especially during the first few charge and discharge processes, the bis(fluorosulfonyl)imide anion (FSI-anion) and the sulfur-oxygen double bond in the electrolyte can form a structure having the highest occupied molecular orbital (high HOMO orbital energy level) in the molecule, so the structure has stronger reducibility, and during the charge and discharge process of the electrochemical device, a uniform and stable electrochemical interface (CEI) film can be formed on the surface of the positive electrode plate, and the structure can reduce the formation of interfacial acidic gases, and can reduce the risk of acidic gas corrosion of the positive electrode active material, thereby improving the chemical properties and structural stability of the positive electrode active material, and improving the mechanical properties of the positive electrode material layer, thereby improving the anti-drop performance of the electrochemical device, effectively reducing the risk of increased AC impedance of the electrochemical device under high voltage (>4.45V), and improving the intermittent cycle performance of the electrochemical device.

[0025] In other embodiments of the present application, 2≤B / A≤4. For example, the value of B / A can be 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5, 3.8, 4 or a range consisting of any two of these values. When the electrolyte includes lithium bis(fluorosulfonyl)imide and a sulfur-containing compound, and satisfies the value of B / A within the scope of the present application, during the charge and discharge process of the electrochemical device, especially during the first few charge and discharge processes, the FSI- anion and the sulfur-oxygen double bond can form a structure with a high HOMO orbital energy level, and therefore has a stronger reducibility, which is conducive to the formation of a uniform and stable CEI film, and the structure can reduce the formation of interfacial acidic gases, and can reduce the risk of acidic gas corrosion of the positive electrode active material, thereby improving the chemical properties and structural stability of the positive electrode material, thereby improving the anti-drop performance of the electrochemical device, effectively reducing the risk of increased AC impedance of the electrochemical device under high voltage, and improving the intermittent cycle performance of the electrochemical device.

[0026] In some embodiments of the present application, 2≤B / A≤3.5. For example, the value of B / A can be 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5 or a range consisting of any two of these values. By regulating the value of B / A within the above range, in the subsequent charge and discharge process after the first few charge and discharge, the CEI film formed by the FSI-anion and the sulfur-oxygen double bond in the electrolyte can maintain a stable membrane structure in the subsequent redox process, which can be more conducive to reducing the formation of interfacial acidic gases and further reducing the risk of acidic gas corrosion of the positive electrode active material, thereby improving the chemical stability of the positive electrode active material, reducing the AC impedance of the electrochemical device under high voltage, and improving the anti-drop performance and intermittent cycle performance of the electrochemical device.

[0027] In some embodiments of the present application, 2.5≤B / A≤3. For example, the value of B / A can be 2.5, 2.55, 2.6, 2.65, 2.7, 2.75, 2.8, 2.85, 2.9, 2.95, 3 or a range consisting of any two of these values. By regulating the value of B / A within the above range, during the charge and discharge process, the CEI film formed by the FSI-anion and the sulfur-oxygen double bond in the electrolyte can further maintain a stable membrane structure in the subsequent redox process, which can be more conducive to reducing the formation of interfacial acidic gases and further reducing the risk of acidic gas corrosion of the positive electrode active material, thereby improving the chemical stability of the positive electrode active material, reducing the AC impedance of the electrochemical device under high voltage, and improving the anti-drop performance and intermittent cycle performance of the electrochemical device.

[0028] In some embodiments of the present application, 0.2≤A≤1.5. For example, the value of A can be 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5 or a range consisting of any two of these values. Lithium bis(fluorosulfonyl)imide has high structural stability. By regulating the value of A within the above range, the viscosity of the electrolyte is moderate, which is conducive to reducing the uneven thickness of the CEI film, which makes the electrolyte flow rate uneven, resulting in an increase in the side reaction of the local area of ​​the positive electrode sheet and the risk of an increase in the byproducts of the reaction between the electrolyte and part of the positive active material. At the same time, it reduces the risk of expansion and gas production of the electrochemical device during the charge and discharge process due to insufficient and uneven stability of the formed CEI film. It is conducive to the formation of a stable and uniform CEI film during the charge and discharge process. This structure can reduce the risk of electrolyte redox decomposition during the charge and discharge reaction, reduce the formation of acidic gases, and improve the chemical stability of the positive electrode active material, reduce the AC impedance of the electrochemical device under high voltage, and improve the anti-drop performance and intermittent cycle performance of the electrochemical device.

[0029] In some embodiments of the present application, 0.5≤B≤4. For example, the value of B can be 0.5, 0.8, 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5, 3.8, 4 or a range consisting of any two of the values. Sulfur-containing compounds have high structural stability. By regulating the value of B within the above range, the viscosity of the electrolyte is moderate, which is conducive to reducing the uneven thickness of the CEI film, which makes the electrolyte flow rate uneven, resulting in an increase in the risk of side reactions in the local area of ​​the positive electrode sheet and an increase in the byproducts of the reaction between the electrolyte and part of the positive electrode active material, while reducing the risk of expansion and gas production of the electrochemical device during the charge and discharge process due to insufficient stability and unevenness of the formed CEI film. It is conducive to forming a stable and uniform CEI film during the charge and discharge process. This structure can reduce the risk of redox decomposition of the electrolyte during the charge and discharge reaction, reduce the formation of acidic gases, and improve the chemical stability of the positive electrode active material, reduce the AC impedance of the electrochemical device under high voltage, and improve the anti-drop performance and intermittent cycle performance of the electrochemical device.

[0030] In some embodiments of the present application, 0.2≤A≤1.5, and 0.5≤B≤4. For example, the value of A can be 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, or a range consisting of any two of them; the value of B can be 0.5, 0.8, 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5, 3.8, 4, or a range consisting of any two of them. Lithium bis(fluorosulfonyl)imide and sulfur-containing compounds have high structural stability. By adjusting the values ​​of A and B within the above range, the viscosity of the electrolyte is moderate, which is conducive to reducing the uneven thickness of the CEI film, which makes the electrolyte flow rate uneven, resulting in an increase in the risk of side reactions in the local area of ​​the positive electrode sheet and an increase in the byproducts of the reaction between the electrolyte and some positive active materials. At the same time, it reduces the risk of expansion and gas production of the electrochemical device during the charge and discharge process due to insufficient stability and unevenness of the formed CEI film. It is conducive to the formation of a stable and uniform CEI film during the charge and discharge process. This structure can reduce the risk of electrolyte redox decomposition during the charge and discharge reaction, reduce the formation of acidic gas, and improve the chemical stability of the positive active material, reduce the AC impedance of the electrochemical device under high voltage, and improve the anti-drop performance and intermittent cycle performance of the electrochemical device.

[0031] The electrolyte of the first aspect of the present application further comprises propyl propionate, and based on the mass of the electrolyte, the mass percentage of propyl propionate is D%, and 30≤D≤40. For example, the value of D can be 30, 30.5, 31, 31.5, 32, 32.5, 33, 33.5, 34, 34.5, 35, 35.5, 36, 36.5, 37, 37.5, 38, 38.5, 39, 39.5, 40, or a range consisting of any two of the values. By selecting an electrolyte including propyl propionate and regulating the value of D within the above range, the risk of increased AC impedance value of the electrochemical device under high voltage conditions can be effectively reduced, and propyl propionate is conducive to a more uniform distribution of FSI- anions, and a more uniform LiF-containing CEI film can be formed at the interface between the positive electrode plate and the electrolyte. This structure has good high-voltage resistance, improves the chemical stability of the positive electrode active material, can effectively reduce the generation of acidic gas in the electrochemical device during the heating process, and improves the anti-drop performance and intermittent cycle performance of the electrochemical device.

[0032] In some embodiments of the present application, 30.5≤A+D≤41. For example, the value of A+D can be 30.5, 31, 31.5, 32, 32.5, 33, 33.5, 34, 34.5, 35, 35.5, 36, 36.5, 37, 37.5, 38, 38.5, 39, 39.5, 40, 40.5, 41, or a range consisting of any two values ​​therein. By regulating the value of A+D within the above range, lithium bis(fluorosulfonyl)imide and propyl propionate act synergistically, and propyl propionate can make the distribution of FSI- anions more uniform, which is beneficial to the formation of a more uniform LiF-containing CEI film at the interface between the positive electrode plate and the electrolyte. This structure has good high-voltage resistance, can effectively reduce the generation of acidic gases in the electrochemical device during the heating process, and reduce the risk of acidic gases corroding the positive electrode active materials, thereby improving the chemical properties and structural stability of the positive electrode active materials, thereby improving the anti-drop performance of the electrochemical device, and can effectively reduce the risk of increased AC impedance values ​​of the electrochemical device under high-voltage conditions, thereby improving the anti-drop performance and intermittent cycle performance of the electrochemical device.

[0033] In some embodiments of the present application, the sulfur-containing compounds include 1,3-propane sultone, 1-fluoro-1,3-propane sultone, 2-fluoro-1,3-propane sultone, 3-fluoro-1,3-propane sultone, 1-methyl-1,3-propane sultone, 2-methyl-1,3-propane sultone, 3-methyl-1,3-propane sultone, 1-propylene-1,3-sultone, 2-propylene-1,3-sultone, 1-fluoro-1-propylene-1,3-sultone, 2-fluoro-1-propylene-1,3-sultone, 3-fluoro-1-propylene-1,3-sultone, 1-fluoro-2-propylene-1 ,3-sultone, 2-fluoro-2-propylene-1,3-sultone, 1-methyl-1-propylene-1,3-sultone, 2-methyl-1-propylene-1,3-sultone, 3-methyl-1-propylene-1,3-sultone, 1-methyl-2-propylene-1,3-sultone, 2-methyl-2-propylene-1,3-sultone, 3-methyl-2-propylene-1,3-sultone, 1,4-butane sultone, 1,5-pentane sultone, methylene disulfonate, ethylene disulfonate, cyclopentane, methyl cyclopentane, 4,5-dimethyl cyclopentane or cyclobutene sulfone. In some embodiments of the present application, the sulfur-containing compound includes at least one of 1,3-propane sultone or cyclopentane sulfone.

[0034] By selecting the sulfur-containing compounds within the above-mentioned range, the sulfur-containing compounds have higher structural stability, and are conducive to reducing the risk of hexafluorophosphate anions decomposing to form HF gas molecules, which can improve the structural stability of the interface between the positive electrode and the electrolyte, and can make the generated lithium-containing reduction products uniformly deposited on the negative electrode, thereby reducing the irreversible capacity in the electrochemical device and improving the intermittent cycle performance of the electrochemical device. And effectively improve the drop test pass rate of the electrochemical device, thereby improving the anti-drop performance of the electrochemical device.

[0035] In some embodiments of the present application, the electrolyte further comprises 3-bromo-5-chloro-1-phenylthiophene, and the mass percentage of 3-bromo-5-chloro-1-phenylthiophene is C%, based on the mass of the electrolyte, and 1.8≤C≤3.8. For example, the value of C can be 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, or a range consisting of any two of the values. By selecting an electrolyte including 3-bromo-5-chloro-1-phenylthiophene and regulating the value of C within the above range, it is beneficial to further form a uniform and stable solid electrolyte interface (SEI) film structure, and effectively improve the drop test pass rate of the electrochemical device, and improve the anti-drop performance of the electrochemical device; the generated lithium-containing reduction product can be uniformly deposited on the negative electrode sheet, thereby reducing the irreversible capacity in the electrochemical device, while reducing the generation of gas in the electrochemical device during the heating process, and improving the intermittent cycle performance of the electrochemical device.

[0036] In some embodiments of the present application, 2≤A+C≤4.8. For example, the value of A+C can be 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5, 3.8, 4, 4.2, 4.5, 4.8 or a range consisting of any two of these values. By regulating the value of A+C within the above range, it is beneficial to further form a uniform and stable CEI film and SEI film, reduce the formation of acidic gas at the interface between the positive electrode plate and the electrolyte, and reduce the risk of acidic gas corrosion of the positive electrode active material, thereby improving the chemical properties and structural stability of the positive electrode active material, effectively improving the drop test pass rate of the electrochemical device, thereby improving the anti-drop performance of the electrochemical device, effectively reducing the risk of increased AC impedance of the electrochemical device under high voltage, and improving the intermittent cycle performance of the electrochemical device. At the same time, the generated lithium-containing reduction product can be uniformly deposited on the negative electrode plate, thereby reducing the irreversible capacity in the electrochemical device, while reducing the generation of gas in the electrochemical device during the heating process, and further improving the intermittent cycle performance of the electrochemical device.

[0037] In other embodiments of the present application, the electrolyte may also include at least one of vinyl sulfate (DTD) or vinylene sulfate (VC), and may further include at least one of fluoromethyl methyl carbonate, difluoromethyl methyl carbonate, trifluoromethyl methyl carbonate, trifluoroethyl methyl carbonate or bis(trifluoroethyl) carbonate.

[0038] In other embodiments of the present application, in addition to LiFSI, the electrolyte further includes an ionizable lithium salt, and the ionizable lithium salt includes at least one of LiPF6, LiSbF6, LiAsF6, LiClO4, LiN(C2F5SO2)2, CF3SO3Li, LiC(CF3SO2)3 or LiC4BO8. The concentration of the ionizable lithium salt in the electrolyte is not particularly limited, and is preferably 0.5 mol / L or more, more preferably 0.8 mol / L or more, and further preferably 1.0 mol / L or more. In addition, it is preferably 3 mol / L or less, more preferably 2 mol / L or less, and further preferably 1.7 mol / L or less. By regulating the concentration of the ionizable lithium salt within the above range, the number of movable lithium ions in the electrolyte is large, and the viscosity of the electrolyte is moderate, so that the electrolyte impedance is low and the lithium ion migration rate is fast, thereby improving the performance of the electrochemical device.

[0039] In other embodiments of the present application, the electrolyte further comprises at least one of fluoroether, fluoroethylene carbonate or ether solvent. In other embodiments of the present application, the electrolyte may further comprise a non-aqueous solvent. The non-aqueous solvent may be a carbonate compound, a carboxylate compound, an ether compound, other organic solvents or a combination thereof.

[0040] The carbonate compound may include not only a chain carbonate compound, but also a cyclic carbonate compound, a fluorinated carbonate compound or a combination thereof.

[0041] The linear carbonate compound can include diethyl carbonate (DEC), ethyl propionate (EP), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC) and combinations thereof. The example of the cyclic carbonate compound is ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC) or combinations thereof. The example of the fluorinated carbonate compound is fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate or combinations thereof.

[0042] Examples of the carboxylic acid ester compound are methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, decanolide, valerolactone, mevalonolactone, caprolactone, methyl formate, or a combination thereof.

[0043] Examples of the ether compound are dibutyl ether, tetraglyme, diglyme, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, or a combination thereof.

[0044] Examples of other organic solvents are dimethyl sulfoxide, 1,2-dioxolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate and phosphoric acid esters or combinations thereof.

[0045] The second aspect of the present application provides an electrochemical device, which includes a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte in any of the foregoing embodiments. The positive electrode sheet and the negative electrode sheet are separated by a separator disposed therebetween. In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode material layer disposed on the positive electrode current collector, the positive electrode material layer may include a positive electrode active material and a first compound, and the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on the negative electrode current collector, and the negative electrode material layer may include a negative electrode active material. Therefore, the electrochemical device of the present application has a low AC impedance under high voltage, and has good anti-drop performance and intermittent cycle performance.

[0046] In some embodiments of the present application, the positive electrode sheet includes a positive electrode material layer, and the positive electrode material layer includes amorphous carbon; a ball with a diameter of 15 mm and a weight of 12 g falls on the positive electrode material layer from a height of 0.1 m to 0.5 m, and the thickness change rate of the positive electrode material layer is 1% to 20%. For example, the falling height of the ball can be 0.1 m, 0.15 m, 0.2 m, 0.25 m, 0.3 m, 0.35 m, 0.4 m, 0.45 m, 0.5 m, or a range consisting of any two of the values; the thickness change rate of the positive electrode material layer can be 1%, 3%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, or a range consisting of any two of the values. When the positive electrode plate meets the above conditions, the positive electrode plate has good conductivity, and the positive electrode plate has mechanical strength and hardness suitable for the electrolyte of the present application. The positive electrode plate and the electrolyte work synergistically to effectively improve the high-temperature puncture resistance, low-temperature cycle performance and high-temperature cycle performance of the electrochemical device, reduce the risk of increased AC impedance of the electrochemical device under high voltage, and improve the intermittent cycle performance of the electrochemical device and the anti-drop performance of the electrochemical device.

[0047] In some embodiments of the present application, the positive electrode material layer includes a first compound, the first compound includes at least one of polybutyl acrylate, polyethyl acrylate, polybutyl methacrylate or polymethyl methacrylate, and the mass percentage of the first compound is 0.01% to 0.28% based on the mass of the positive electrode material layer. For example, the mass percentage of the first compound can be 0.01%, 0.03%, 0.05%, 0.08%, 0.10%, 0.12%, 0.15%, 0.18%, 0.20%, 0.22%, 0.25%, 0.28% or a range consisting of any two of the values. By selecting the first compound of the above type and regulating the mass percentage of the first compound within the above range, the positive electrode plate has good wetting properties suitable for the electrolyte of the present application. The positive electrode plate and the electrolyte work synergistically to effectively improve the electrochemical high-temperature puncture resistance, low-temperature cycle performance and high-temperature cycle performance, reduce the risk of increased AC impedance of the electrochemical device under high voltage, improve the intermittent cycle performance of the electrochemical device, and take into account the anti-drop performance of the electrochemical device.

[0048] In some embodiments of the present application, the thermal shrinkage rate of the diaphragm in the width direction after the diaphragm is unfolded at 160°C is F%, the thickness of the positive electrode sheet is Tμm, and 0.04≤F / T≤0.1. For example, the value of F / T can be 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, or a range consisting of any two of the values. By regulating the value of F / T within the above range, the diaphragm and the positive electrode sheet work together, and the electrochemical device has better high-temperature cycle performance and structural stability, and also has better high-temperature puncture resistance.

[0049] In the present application, the thickness of the positive electrode sheet is the sum of the thickness of the positive electrode current collector and the thickness of the positive electrode material layer. The thickness of the positive electrode material layer is regulated by means known to those skilled in the art. For example, when the positive electrode slurry is coated on the surface of the positive electrode current collector, the thickness of the positive electrode material layer can be increased by increasing the coating weight per unit area of ​​the positive electrode material layer, and the thickness of the positive electrode material layer can be reduced by reducing the coating weight per unit area of ​​the positive electrode material layer. When other conditions are constant, the thickness of the positive electrode material layer can be reduced by increasing the compaction density when the positive electrode sheet is cold pressed, and the thickness of the positive electrode material layer can be increased by reducing the compaction density.

[0050] In other embodiments of the present application, 0.2≤F≤6. For example, the value of F can be 0.2, 0.5, 0.8, 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5, 3.8, 4, 4.2, 4.5, 4.8, 5, 5.2, 5.5, 5.8, 6, or a range consisting of any two of the values. By regulating the value of F within the above range, the diaphragm has good thermal stability, the electrochemical device has better high temperature cycle performance and structural stability, and also has better high temperature puncture resistance.

[0051] In some embodiments, the negative electrode plate may include a negative electrode current collector and a negative electrode material layer disposed on the negative electrode current collector. The negative electrode material layer may be disposed on one or both sides of the negative electrode current collector. In some embodiments, the negative electrode current collector may be at least one of a copper foil, a nickel foil, or a carbon-based current collector. In some embodiments, the thickness of the negative electrode current collector may be 1 μm to 200 μm. In some embodiments, the negative electrode material layer may be coated only on a partial area of ​​the negative electrode current collector. In some embodiments, the thickness of the negative electrode material layer may be 10 μm to 500 μm. It should be understood that these are exemplary only and other suitable thicknesses may be used.

[0052] In some embodiments, as described above, the negative electrode material layer includes a negative electrode active material. In some embodiments, the negative electrode active material includes at least one of natural graphite, artificial graphite, or a silicon-based material. In some embodiments, the silicon-based material includes at least one of silicon, a silicon-oxygen compound, a silicon-carbon compound, or a silicon alloy.

[0053] In some embodiments, the negative electrode material layer may also include a negative electrode conductor and / or a negative electrode binder. The negative electrode conductor may include at least one of carbon black, acetylene black, Ketjen black, graphene, carbon nanotubes, or carbon fibers. In some embodiments, the negative electrode binder may include at least one of carboxymethyl cellulose (CMC), polyacrylic acid, polyacrylate, polyacrylate, polyvinyl pyrrolidone, polyimide, polysiloxane, or styrene-butadiene rubber. It should be understood that the materials disclosed above are only exemplary, and the negative electrode active material layer may be any other suitable material. In some embodiments, the mass ratio of the negative electrode active material, the negative electrode conductor, and the negative electrode binder in the negative electrode active material layer may be (80 to 99): (0.5 to 10): (0.5 to 10), and it should be understood that this is only exemplary and not intended to limit the present application.

[0054] In some embodiments, the positive electrode plate includes a positive electrode current collector and a positive electrode material layer disposed on the positive electrode current collector. The positive electrode active material layer may be located on one side or both sides of the positive electrode current collector. In some embodiments, the positive electrode current collector may be made of aluminum foil, and of course, other positive electrode current collectors commonly used in the art may also be used. In some embodiments, the thickness of the positive electrode current collector may be 1 μm to 200 μm. In some embodiments, the positive electrode material layer may be coated only on a partial area of ​​the positive electrode current collector. In some embodiments, the thickness of the positive electrode active material layer may be 20 μm to 490 μm, and further preferably, the thickness may be 20 μm to 400 μm, and further, it may be 40 μm to 120 μm, and further, it may be 40 μm to 90 μm.

[0055] In some embodiments, as described above, the positive electrode active material layer includes a positive electrode active material. In some embodiments, the positive electrode active material may include at least one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, or lithium nickel manganese oxide, and the above positive electrode active material may be doped and / or coated. Further preferably, the positive electrode active material is lithium cobalt oxide or lithium iron phosphate.

[0056] In some embodiments, at least part of the surface of the positive electrode material layer is provided with a covering layer, the covering layer includes lithium phosphate and / or lithium niobate, the mass ratio of the two substances is 1:3 to 1:1, and the thickness of the covering layer is 1 μm to 1.8 μm. Through the above arrangement, the positive electrode sheet has better conductivity and makes the structure of the positive electrode active material more stable, which is conducive to improving the voltage drop and intermittent cycle performance of the electrochemical device at high temperature.

[0057] In some embodiments, the positive electrode plate further includes a first material layer, and the first material layer is located between the positive electrode material layer and the positive electrode current collector. The first material layer includes lithium dihydrogen phosphate or aluminum dihydrogen phosphate, and the mass percentage of lithium dihydrogen phosphate or aluminum dihydrogen phosphate is W%, 5≤W≤20 based on the total mass of the first material layer. Through the above arrangement, the positive electrode plate has better conductivity and makes the physical and chemical structure of the positive electrode active material more stable, which is conducive to improving the voltage drop and intermittent cycle performance of the electrochemical device at high temperature.

[0058] In some embodiments, the positive electrode material layer also includes a positive electrode binder and a positive electrode conductor. In some embodiments, the positive electrode binder may include polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, styrene-acrylate copolymer, styrene-butadiene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinyl acetate, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene or polyhexafluoropropylene. In some embodiments, the positive electrode conductor may include at least one of conductive carbon black, acetylene black, Ketjen black, graphene, carbon nanotubes or carbon fibers.

[0059] In some embodiments, the substrate of the separator includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid. For example, polyethylene includes at least one selected from high-density polyethylene, low-density polyethylene or ultra-high molecular weight polyethylene. Especially polyethylene and polypropylene, they have a good effect on preventing short circuits and can improve the safety of the battery through the shutdown effect. In some embodiments, the thickness of the separator as a whole is in the range of about 3 μm to 480 μm.

[0060] In some embodiments, the surface of the diaphragm may further include a porous layer, the porous layer being disposed on at least one surface of the diaphragm, the porous layer comprising inorganic particles and a binder, the inorganic particles being selected from at least one of aluminum oxide (Al2O3), silicon oxide (SiO2), magnesium oxide (MgO), titanium oxide (TiO2), hafnium dioxide (HfO2), tin oxide (SnO2), cerium dioxide (CeO2), nickel oxide (NiO), zinc oxide (ZnO), calcium oxide (CaO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), silicon carbide (SiC), boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, or barium sulfate. In some embodiments, the pores of the diaphragm have a diameter in the range of about 0.01 μm to 1 μm. The binder of the porous layer is selected from at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethylcellulose, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene, or polyhexafluoropropylene. The porous layer on the surface of the diaphragm can improve the heat resistance, oxidation resistance and electrolyte wetting performance of the diaphragm, and enhance the adhesion between the diaphragm and the pole piece. One surface of the diaphragm can also include a high melting point crystalline polymer or a high temperature resistant amorphous polymer. The high temperature resistant resin includes at least one of polypropylene, poly-4-methylpentene, polytetrafluoroethylene, polyvinylidene fluoride and cycloolefin copolymers. The high melting point crystalline polymer includes at least one of polypropylene, poly-4-methylpentene, polytetrafluoroethylene or polyvinylidene fluoride, and the high temperature resistant amorphous polymer includes cycloolefin copolymers. Based on the mass of the polyolefin porous substrate, the mass percentage z of the high temperature resistant resin is 2.5% to 9%. For example, the mass percentage z of the high temperature resistant resin is 2.5%, 3%, 5%, 7%, 8%, 9% or a range composed of any two of the values. When the above-mentioned types of high temperature resistant resins are added to the polyolefin porous substrate and the mass percentage of the high temperature resistant resin is regulated within the above range, it is beneficial to increase the melting temperature of the diaphragm, improve the strength and high temperature performance of the electrochemical device.

[0061] In some embodiments, the electrochemical device is a lithium-ion battery, but the present application is not limited thereto.

[0062] In some embodiments of the present application, taking lithium-ion batteries as an example, the positive electrode sheet, the isolation membrane, and the negative electrode sheet are wound or stacked in sequence to form an electrode assembly, and then placed in a shell such as an aluminum-plastic film for packaging, and the electrolyte is injected, formed, and packaged to make a lithium-ion battery.

[0063] The third aspect of the present application provides an electronic device, which includes the electrochemical device in any of the above embodiments. Therefore, the electronic device of the present application has good performance.

[0064] The present application does not specifically limit the type of electronic device, which can be any electronic device known in the prior art. In some embodiments, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0065] Example

[0066] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.

[0067] Test methods and equipment:

[0068] Capacity retention test after 300 cycles of intermittent cycling at 60°C:

[0069] At 60°C, the lithium-ion battery was allowed to stand for 30 minutes; it was charged to 4.5V at a constant current of 0.5C, and then charged to 0.05C at a constant voltage of 4.5V; the lithium-ion battery was then allowed to stand in a 60°C environment for 24 hours; the lithium-ion battery was then discharged to 3.0V at a constant current of 0.5C, and the discharge capacity of the lithium-ion battery was recorded; this was a complete intermittent charge and discharge cycle, and the lithium-ion battery was charged and discharged 300 times in the same way.

[0070] Capacity retention rate after 300 intermittent cycles at 60°C (%) = discharge capacity at the 300th cycle / first discharge capacity × 100%.

[0071] Among them, the higher the capacity retention rate after 300 intermittent cycles at 60°C, the better the intermittent cycle performance of the lithium-ion battery.

[0072] Lithium-ion battery AC impedance test:

[0073] At 25°C, the assembled lithium-ion battery was left to rest for 12 hours, and then the electrochemical workstation was used to test the alternating current impedance spectrum (EIS) of the lithium-ion battery. The test frequency was 105Hz and the test amplitude was 10mV. The charge and discharge cycle steps of "300 cycles of intermittent cycle capacity retention test at 60°C" were followed for 300 cycles, and then the impedance change rate was calculated by the following formula:

[0074] The change rate of AC internal resistance before and after 300 cycles (%) = [(impedance after 300 cycles - impedance before 300 cycles) / impedance before 300 cycles] × 100%.

[0075] Drop test pass rate test:

[0076] (1) Under the environmental condition of 25℃, record the open circuit voltage and internal resistance of the lithium-ion battery (the test instrument is a voltage resistance tester, manufacturer: Dongguan Lijia Precision Instrument Co., Ltd., model: LNG-SY1-0020-DQ); (2) Put the lithium-ion battery into the fixture bin, and use the automatic drop device to drop the fixture bin with the lithium-ion battery from a position of 1m to the cement bottom plate in a round of landing on the bottom surface, left side, right side, back side, front side and top side of the fixture bin head. One cycle is a total of 3 rounds, i.e. 18 times; (3 ) Then drop the battery from a position of 1.5 m to a cement floor in a cycle of landing on the bottom, left side, right side, back side, front side and top side of the fixture head. A total of 3 drops, i.e. 18 times, are performed in one cycle; (4) after each drop, measure the voltage of the lithium-ion battery. If the lithium-ion battery catches fire or leaks, stop dropping it; otherwise, continue dropping it; (5) record the voltage and internal resistance of the lithium-ion battery. If the voltage drop is less than 10 mV and the VOC organic gas detection is less than 500 ppm within 24 hours, the lithium-ion battery is judged to have passed the drop test.

[0077] In each group of embodiments or comparative examples, 50 lithium-ion batteries are prepared and tested. The number of lithium-ion batteries that pass the test is X, and the drop test pass rate of the lithium-ion batteries in this group = X / 50×100 (%).

[0078] Among them, the higher the drop test pass rate, the better the drop protection performance of the lithium-ion battery pack.

[0079] -20℃ cycle 300 cycles capacity retention test:

[0080] The lithium ion batteries of the embodiments and comparative examples were repeatedly charged and discharged by the following steps, and the discharge capacity retention rate of the lithium ion batteries was calculated.

[0081] In an environment of -20°C, the first charge and discharge were carried out. Constant current charging was carried out at a charging current of 2C to a full charge voltage of 4.5V, and then constant voltage charging was carried out at a maximum voltage of 4.5V until the current was 0.02C, and then constant current discharge was carried out at a discharge current of 0.5C until the final voltage was 3.0V, and the discharge capacity of the first cycle was recorded; then the above steps were repeated for 300 charge and discharge cycles, and the discharge capacity of the 300th cycle was recorded.

[0082] Capacity retention rate after 300 cycles at -20°C = (discharge capacity at the 300th cycle / discharge capacity at the first cycle) x 100%.

[0083] Among them, the higher the capacity retention rate after 300 cycles at -20℃, the better the low-temperature cycle performance of the lithium-ion battery.

[0084] Capacity retention test after 500 cycles at 45°C:

[0085] The lithium ion batteries of the embodiments and comparative examples were repeatedly charged and discharged by the following steps, and the discharge capacity retention rate of the lithium ion batteries was calculated.

[0086] In an environment of 45°C, the first charge and discharge were carried out. Constant current charging was carried out at a charging current of 2C to a full charge voltage of 4.5V, and then constant voltage charging was carried out at the maximum voltage until the current was 0.02C, and then constant current discharge was carried out at a discharge current of 0.5C until the final voltage was 3.0V, and the discharge capacity of the first cycle was recorded; then the above steps were repeated for 300 charge and discharge cycles, and the discharge capacity of the 500th cycle was recorded.

[0087] Capacity retention rate after 500 cycles at 45° C. (%)=(discharge capacity at the 500th cycle / discharge capacity at the first cycle)×100%.

[0088] Among them, the higher the capacity retention rate after 500 cycles at 45°C, the better the high-temperature cycle performance of the lithium-ion battery.

[0089] 40℃ puncture test:

[0090] The lithium-ion battery to be tested is charged at a constant current of 0.05C to the designed full charge voltage of 4.5V, and then charged at the designed full charge voltage of 4.5V to a current of 0.025C, so that the lithium-ion battery reaches a fully charged state, and the appearance of the lithium-ion battery before the test is recorded. The lithium-ion battery is subjected to a nail penetration test in an environment of 25±3℃, with a steel nail diameter of 4mm and a penetration speed of 30mm / s. The nail penetration position is located at the geometric center of the lithium-ion battery. The test is stopped after 3.5min or when the surface temperature of the electrode assembly drops to 50℃. Ten lithium-ion batteries are grouped together to observe the state of the lithium-ion battery during the test, and the judgment standard is that the lithium-ion battery does not burn or explode.

[0091] Among them, the more the number of cells that pass the 40°C puncture test, the stronger the high-temperature puncture resistance of the lithium-ion battery.

[0092] Electrolyte component test:

[0093] The electrolyte components were tested using a gas chromatography-mass spectrometer (GC-MS, model: Agilent GC 7890A), and the external standard method was used to test the components to measure the mass percentage of each component in the electrolyte.

[0094] Thermal shrinkage test of the diaphragm in the width direction after the diaphragm is unfolded:

[0095] At an ambient temperature of 25°C, the lithium-ion batteries in the tested embodiments and comparative examples were discharged at 0.5C to 2.5V and then disassembled, the diaphragms were taken out, and the electrolyte residues were removed by soaking in dimethyl carbonate (DMC) for 20 min. The diaphragms were then placed in an oven and dried at 60°C for 12 h to obtain diaphragm samples.

[0096] The membrane sample was cut into a size of 5 cm × 5 cm, spread flat on a glass plate, placed in a 200°C oven, and allowed to stand for 2 h. The degree of membrane edge curling was observed, and the corresponding dimensions A cm × B cm were measured.

[0097] Then, the heat shrinkage rate F% of the separator in the width direction after the separator is unfolded = (5-A) / 5×100%.

[0098] Thickness change rate test of positive electrode material layer:

[0099] At an ambient temperature of 25°C, the lithium-ion batteries of the embodiments and comparative examples were discharged to 2.5V at 0.5C and then disassembled to take out the positive electrode sheets, which were soaked in dimethyl carbonate (DMC) for 20 min. The positive electrode sheets were then placed in an oven and dried at 60°C for 12 h to obtain test samples of the positive electrode sheets.

[0100] Take a 3cm×3cm positive electrode sheet sample at the center of the plane formed by the length direction and the width direction after the positive electrode sheet is unfolded, measure the thickness H1 of the positive electrode material layer of the 3cm×3cm positive electrode sheet sample (take any 3 points to calculate the average value), use a ball with a diameter of 15mm and a weight of 12g to drop on the positive electrode material layer of the 3cm×3cm positive electrode sheet sample from a height of 0.4m, so that the ball falls completely on the positive electrode material layer, take 3 points to measure the average thickness H2 of the positive electrode material layer after being impacted, then the thickness change rate (%) of the positive electrode material layer = H2 / H1×100(%).

[0101] Example 1-1

[0102] <Preparation of positive electrode sheet>

[0103] The positive electrode active material lithium cobalt oxide LiCoO2, the conductive agent amorphous carbon, the binder polyvinylidene fluoride (PVDF), and the first compound polybutyl acrylate are mixed in a mass ratio of 96.75:1:2:0.25, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry with a solid content of 65wt%. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 12μm, and the aluminum foil is dried at 120℃ for 1h to obtain a positive electrode sheet coated with a positive electrode material layer on one side. The above steps are repeated on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode material layer on both sides. Then, after cold pressing, cutting, and welding the pole ears, it is dried under vacuum conditions at 120℃ for 1h to obtain a positive electrode sheet with a size of 74mm (width) × 867mm (length) with a current collector empty foil area at the tail. Among them, the coating weight per unit area of ​​the single-sided positive electrode material layer is 250mg / 1540.25mm 2 , the thickness T of the positive electrode sheet after cold pressing is 60μm.

[0104] Alumina (Dv99 is 0.7 μm) and binder PVDF are mixed in a mass ratio of 80:20, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain an inorganic coating slurry with a solid content of 30 wt%. The inorganic coating slurry is first evenly coated on one surface of the positive current collector aluminum foil at the tail of the above-mentioned positive electrode sheet (this surface is defined as the a surface, and the other surface of the current collector is defined as the b surface), and dried at 120°C for 1 hour to obtain a positive electrode sheet with an inorganic coating on one surface of the current collector, i.e., the a surface, the length of the inorganic coating is 95 mm, and the thickness of the inorganic coating is 2.5 μm.

[0105] <Preparation of negative electrode sheet>

[0106] The negative electrode active material artificial graphite, conductive agent conductive carbon black, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) are mixed in a weight ratio of 96.5:1.5:1:1, deionized water is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain a negative electrode slurry, wherein the solid content of the negative electrode slurry is 75wt%. The negative electrode slurry is evenly coated on one side of the negative electrode collector copper foil, and dried at 120°C to obtain a negative electrode sheet coated with a negative electrode material layer on one side, and the above steps are repeated on the other side of the negative electrode collector copper foil to obtain a negative electrode sheet coated with a negative electrode material layer on both sides, and then after cold pressing, cutting, and slitting, a negative electrode sheet with a specification of 76mm (width) × 874mm (length) is obtained. Among them, the unit area coating weight of the single-sided negative electrode material layer is 90mg / 1540.25mm 2 The thickness of the negative electrode sheet after cold pressing is 70μm.

[0107] <Preparation of Electrolyte>

[0108] In a glove box filled with argon, EC (ethylene carbonate) was first heated at a high temperature of 60°C to convert it into a liquid state, and then a base solvent was prepared with a mass ratio of EC (ethylene carbonate): DEC (diethyl carbonate): EMC (ethyl methyl carbonate): PC (propylene carbonate) = 1:1:1:1, and then solid lithium hexafluorophosphate was added to prepare a 1.15 mol / L lithium hexafluorophosphate solution by a constant volume method, and solid LiFSI accounting for 1.0% of the total mass of the electrolyte was added, that is, the value of A was 1; finally, add adiponitrile and 1,3,6-hexanetrinitrile, so that the mass content of adiponitrile accounts for 1% of the total mass of the entire electrolyte, the mass content of 1,3,6-hexanetrinitrile accounts for 1.5% of the total mass of the entire electrolyte, add 1,3-propanesultone accounting for 2.0% of the total mass of the electrolyte, 3-bromo-5-chloro-1-phenylthiophene accounting for 1.8% of the total mass of the electrolyte and propyl propionate accounting for 30% of the total mass of the electrolyte, that is, the value of B is 2, the value of C is 1.8, the value of D is 30, and the remainder is the base solvent.

[0109] <Preparation of Separator>

[0110] A 10 μm thick polyethylene (PE) microporous membrane was selected as the substrate of the separator.

[0111] Inorganic boehmite particles with a Dv50 of 1.3 μm were mixed with polyacrylate in a mass ratio of 88:12 and dissolved in deionized water to form an inorganic coating slurry with a solid content of 43%. The resulting inorganic coating slurry was then evenly coated on one side of the PE base film using a micro-concave coating method to obtain a heat-resistant layer, which was then dried in an oven. The thickness of the inorganic coating was 1.8 μm.

[0112] Organic coating preparation:

[0113] Add the first polymer polypropylene (PP) polymer particles with propylene as the base monomer into the stirrer and stir evenly; add sodium carboxymethyl cellulose into the stirrer and stir evenly; add dimethyl siloxane, a wetting agent, into the stirrer, then add deionized water and stir, adjust the viscosity of the slurry to 45mPa·s and the solid content to 6%, and obtain an organic coating slurry. The organic coating slurry is evenly coated on the inorganic coating on one side of the base film, and after drying in an oven, a first coating is obtained. The thickness of the first coating is 3μm. The mass ratio of the first polymer, sodium carboxymethyl cellulose, and dimethyl siloxane is 95:0.5:4.5. Among them, the polymer is spherical or quasi-spherical in the isolation membrane, and the sphericity R of the polymer satisfies 0.7≤R≤1.0.

[0114] Preparation of coating on the other side of the diaphragm:

[0115] Inorganic boehmite particles with a Dv50 of 1.3 μm and polyacrylate were mixed in a mass ratio of 88:12 and dissolved in deionized water to form an inorganic coating slurry with a solid content of 47%. The resulting inorganic coating slurry was then evenly coated on the other side of the PE base film using a micro-concave coating method to obtain a heat-resistant layer, which was dried in an oven. The thickness of the inorganic coating was 1.8 μm.

[0116] The inorganic particle boehmite and the binder polyvinylidene fluoride are mixed at a volume ratio of 1.4, and then N-methylpyrrolidone (a first solvent) is added and uniformly stirred to obtain a coating liquid, wherein the solid content of the coating liquid is 8%; the coating liquid is coated on a porous substrate (polyethylene) by an immersion coating method to form a wet film; the porous substrate (polyethylene) with the wet film is immersed in a coagulation liquid containing deionized water (a third solvent) and N-methylpyrrolidone (NMP, a second solvent), and the second solvent is phase-converted, wherein the mass percentage of N-methylpyrrolidone (a second solvent) in the coagulation liquid is 38%, and the temperatures of the coating liquid and the coagulation liquid are both 25°C; after being immersed in the coagulation liquid for 30 seconds, the membrane is placed in an oven and dried at 60°C to obtain a diaphragm with a porous membrane.

[0117] <Preparation of lithium-ion batteries>

[0118] The positive electrode sheet, the separator and the negative electrode sheet are stacked in order, the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, the side of the separator coated with the organic coating is opposite to the a-side of the positive electrode collector, and the electrode assembly is wound to obtain the electrode assembly. After welding the pole ears, the electrode assembly is placed in an outer packaging aluminum-plastic film, and after dehydration at 80°C, the above-mentioned electrolyte is injected, and after vacuum packaging, standing, formation, shaping, capacity testing and other processes, a lithium-ion battery is obtained.

[0119] Example 1-2 to Example 1-10

[0120] Except for adjusting the relevant parameters according to Table 1, the rest is the same as Example 1-1. When the value of B in the electrolyte changes, the mass percentage of the base solvent changes accordingly, the proportion of each component in the base solvent remains unchanged, and the mass percentage of other substances except the base solvent remains unchanged.

[0121] Embodiment 1-11

[0122] Except for adjusting the relevant parameters according to Table 1, the rest is the same as Example 1-1. Among them, when the values ​​of A and B in the electrolyte change, the mass percentage of the base solvent changes accordingly, the proportion of each component in the base solvent remains unchanged, and the mass percentage of other substances except the base solvent remains unchanged.

[0123] Example 1-12 to Example 1-16

[0124] Except for adjusting the relevant parameters according to Table 1, the rest is the same as Example 1-11. Among them, when the value of A in the electrolyte changes, the mass percentage of the base solvent changes accordingly, the proportion of each component in the base solvent remains unchanged, and the mass percentage of other substances except the base solvent remains unchanged.

[0125] Example 1-17 to Example 1-20

[0126] Except for adjusting the relevant parameters according to Table 1, the rest is the same as Example 1-14. Among them, when the value of D in the electrolyte changes, the mass percentage of the base solvent changes accordingly, the proportion of each component in the base solvent remains unchanged, and the mass percentage of other substances except the base solvent remains unchanged.

[0127] Example 1-21 to Example 1-25

[0128] Except for adjusting the relevant parameters according to Table 1, the rest is the same as Example 1-20. Among them, when the value of C in the electrolyte changes, the mass percentage of the base solvent changes accordingly, the proportion of each component in the base solvent remains unchanged, and the mass percentage of other substances except the base solvent remains unchanged.

[0129] Examples 1-26

[0130] Except for adjusting the relevant parameters according to Table 1, the rest is the same as Example 1-20. Among them, when the value of B in the electrolyte changes, the mass percentage of the base solvent changes accordingly, the proportion of each component in the base solvent remains unchanged, and the mass percentage of other substances except the base solvent remains unchanged.

[0131] Example 1-27 to Example 1-28

[0132] Except for adjusting the relevant parameters according to Table 1, the rest is the same as Example 1-20. Among them, when the value of D in the electrolyte changes, the mass percentage of the base solvent changes accordingly, the proportion of each component in the base solvent remains unchanged, and the mass percentage of other substances except the base solvent remains unchanged.

[0133] Example 1-29 to Example 1-30

[0134] Except for adjusting the relevant parameters according to Table 1, the rest is the same as Example 1-20. Among them, when the value of C in the electrolyte changes, the mass percentage of the base solvent changes accordingly, the proportion of each component in the base solvent remains unchanged, and the mass percentage of other substances except the base solvent remains unchanged.

[0135] Example 1-31 to Example 1-36

[0136] Except for adjusting the relevant parameters according to Table 1, the rest is the same as Example 1-14.

[0137] Embodiment 1-37

[0138] Except that 3-bromo-5-chloro-1-phenylthiophene and propyl propionate are not added in <Preparation of Electrolyte> and relevant parameters are adjusted according to Table 1, the rest is the same as Example 1-1. Among them, when 1,3-propane sultone and propyl propionate are not added to the electrolyte, the mass percentage of the base solvent changes accordingly, the proportion of each component in the base solvent remains unchanged, and the mass percentage of other substances except the base solvent remains unchanged.

[0139] Examples 1-38

[0140] Except that 3-bromo-5-chloro-1-phenylthiophene is not added in <Preparation of Electrolyte> and the relevant parameters are adjusted according to Table 1, the rest is the same as Example 1-1. Among them, when 1,3-propane sultone is not added to the electrolyte, the mass percentage of the base solvent changes accordingly, the proportion of each component in the base solvent remains unchanged, and the mass percentage of other substances except the base solvent remains unchanged.

[0141] Examples 1-39

[0142] Except that propyl propionate is not added in <Preparation of electrolyte> and relevant parameters are adjusted according to Table 1, the rest is the same as Example 1-1. Among them, when propyl propionate is not added to the electrolyte, the mass percentage of the base solvent changes accordingly, the proportion of each component in the base solvent remains unchanged, and the mass percentage of other substances except the base solvent remains unchanged.

[0143] Example 2-1 to Example 2-22

[0144] Except for adjusting the relevant preparation parameters according to Table 2, the rest is the same as Example 1-1. Among them, when the thickness T of the positive electrode sheet changes, the coating weight per unit area of ​​the positive electrode material layer is adjusted so that the value of T is as shown in Table 2. When the mass percentage of the first compound changes, the mass ratio of the positive electrode active material to the first compound is adjusted so that the mass percentage of the first compound is as shown in Table 2.

[0145] Example 3-1

[0146] Except for preparing the positive electrode sheet according to the following steps, the rest is the same as Example 1-1.

[0147] <Preparation of positive electrode sheet>

[0148] The positive electrode active material lithium cobalt oxide LiCoO2, the conductive agent amorphous carbon, the binder polyvinylidene fluoride (PVDF), and the first compound polybutyl acrylate are mixed in a mass ratio of 96.75:1:2:0.25, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry with a solid content of 65wt%; 2kg of lithium phosphate and lithium niobate are prepared in a mass ratio of 1:2, 0.1kg of conductive carbon and 10kg of deionized water are added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry with a solid content of 65wt%. Stir at a stirring speed of 1300rpm for 2.5h to obtain a covering layer slurry with a solid content of 65wt%; the positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 12μm, and the aluminum foil is dried at 120℃ for 1h to obtain a positive electrode sheet coated with a positive electrode material layer on one side, and the covering layer slurry is coated on the other surface of the positive electrode material layer away from the aluminum foil, and dried at 120℃ for 1h to obtain a positive electrode sheet coated with a positive electrode material layer and a covering layer on one side. Repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode material layer and a covering layer on both sides. Then, after cold pressing, cutting, and welding the pole ears, dry under vacuum conditions at 120℃ for 1h to obtain a positive electrode sheet with a size of 74mm (width) × 867mm (length) and a current collector empty foil area at the tail. Among them, the unit area coating weight of the single-sided positive electrode material layer is 250mg / 1540.25mm 2 After cold pressing, the thickness T of the positive electrode sheet excluding the covering layer is 60 μm, and the thickness of the single-sided covering layer is 1.5 μm.

[0149] Alumina (Dv99 is 0.7 μm) and binder PVDF are mixed in a mass ratio of 80:20, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain an inorganic coating slurry with a solid content of 30 wt%. The inorganic coating slurry is first evenly coated on one surface of the positive current collector aluminum foil at the tail of the above-mentioned positive electrode sheet (this surface is defined as the a surface, and the other surface of the current collector is defined as the b surface), and dried at 120°C for 1 hour to obtain a positive electrode sheet with an inorganic coating on one surface of the current collector, i.e., the a surface, the length of the inorganic coating is 95 mm, and the thickness of the inorganic coating is 2.5 μm.

[0150] Example 3-2 to Example 3-3

[0151] Except for adjusting the relevant preparation parameters according to Table 3, the rest is the same as Example 3-1.

[0152] Embodiment 3-4

[0153] Except for preparing the positive electrode sheet according to the following steps, the rest is the same as Example 1-1.

[0154] <Preparation of positive electrode sheet>

[0155] 4.2545kg of lithium dihydrogen phosphate, 3kg of polyacrylic acid, 28kg of boehmite and 0.2kg of conductive carbon were added to 60kg of deionized water, stirred at a stirring speed of 1300rpm for 2.5h to obtain a first material layer slurry with a solid content of 24wt%; the positive electrode active material lithium cobalt oxide LiCoO2, the conductive agent amorphous carbon, the binder polyvinylidene fluoride (PVDF), and the first compound polybutyl acrylate were mixed in a mass ratio of 96.75:1:2:0.25, N-methylpyrrolidone (NMP) was added, and stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry with a solid content of 65wt%. The first material layer slurry was coated on a positive electrode current collector aluminum foil with a thickness of 12μm, and dried at 120℃ to obtain a positive electrode current collector coated with the first material layer on one side, and the positive electrode slurry was coated on the other surface of the first material layer away from the aluminum foil, and dried at 120℃ for 1h to obtain a positive electrode sheet coated with a positive electrode material layer and a first material layer on one side. Repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode material layer and a first material layer on both sides. Then, after cold pressing, cutting, and welding the tabs, dry it under vacuum at 120°C for 1 hour to obtain a positive electrode sheet with a size of 74mm (width) × 867mm (length) and a current collector empty foil area at the tail. The coating weight per unit area of ​​the single-sided positive electrode material layer is 250mg / 1540.25mm 2 After cold pressing, the thickness T of the positive electrode sheet excluding the first material layer is 60 μm, the thickness of the single-sided first material layer is 1.5 μm, and based on the mass of the first material layer, the mass percentage W of lithium dihydrogen phosphate is 12%.

[0156] Alumina (Dv99 is 0.7 μm) and binder PVDF are mixed in a mass ratio of 80:20, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain an inorganic coating slurry with a solid content of 30 wt%. The inorganic coating slurry is first evenly coated on one surface of the positive current collector aluminum foil at the tail of the above-mentioned positive electrode sheet (this surface is defined as the a surface, and the other surface of the current collector is defined as the b surface), and dried at 120°C for 1 hour to obtain a positive electrode sheet with an inorganic coating on one surface of the current collector, i.e., the a surface, the length of the inorganic coating is 95 mm, and the thickness of the inorganic coating is 2.5 μm.

[0157] Example 3-5 to Example 3-7

[0158] Except for adjusting the relevant preparation parameters according to Table 3, the rest is the same as Example 3-4. When the mass percentage of lithium dihydrogen phosphate changes, the amount of lithium dihydrogen phosphate added is adjusted so that the value of W is as shown in Table 3.

[0159] Comparative Example 1

[0160] Except that 1,3-propane sultone, 3-bromo-5-chloro-1-phenylthiophene and propyl propionate are not added in <Preparation of Electrolyte> and the relevant parameters are adjusted according to Table 1, the rest is the same as Example 1-20. Among them, when 1,3-propane sultone, 1,3-propane sultone and propyl propionate are not added to the electrolyte, the mass percentage of the base solvent changes accordingly, the proportion of each component in the base solvent remains unchanged, and the mass percentage of other substances except the base solvent remains unchanged.

[0161] Comparative Example 2

[0162] Except that lithium bis(fluorosulfonyl)imide, 3-bromo-5-chloro-1-phenylthiophene and propyl propionate are not added in <Preparation of Electrolyte> and relevant parameters are adjusted according to Table 1, the rest is the same as Example 1-20. Among them, when lithium bis(fluorosulfonyl)imide, 1,3-propane sultone and propyl propionate are not added to the electrolyte, the mass percentage of the base solvent changes accordingly, the proportion of each component in the base solvent remains unchanged, and the mass percentage of other substances except the base solvent remains unchanged.

[0163] Comparative Example 3

[0164] Except for adjusting the relevant parameters according to Table 1, the rest is the same as Example 1-11. Among them, when the value of A in the electrolyte changes, the mass percentage of the base solvent changes accordingly, the proportion of each component in the base solvent remains unchanged, and the mass percentage of other substances except the base solvent remains unchanged.

[0165] Comparative Example 4 to Comparative Example 5

[0166] Except for adjusting the relevant parameters according to Table 1, the rest is the same as Example 1-20. Among them, when the value of B in the electrolyte changes, the mass percentage of the base solvent changes accordingly, the proportion of each component in the base solvent remains unchanged, and the mass percentage of other substances except the base solvent remains unchanged.

[0167] The preparation parameters and performance parameters of each embodiment and comparative example are shown in Tables 1 to 3.

[0168] Table 1

[0169]

[0170]

[0171] Note: “ / ” in Table 1 indicates no relevant preparation parameters.

[0172] From Examples 1-1 to 1-39 and Comparative Examples 1 to 5, it can be seen that when the electrolyte includes lithium bis(fluorosulfonyl)imide and sulfur-containing compounds, and the value of B / A is within the scope of this application, the change rate of the AC internal resistance of the lithium-ion battery before and after 300 cycles is low, and the pass rate of the drop test and the capacity retention rate of 300 cycles of intermittent cycles at 60°C are high, indicating that the lithium-ion battery of this application is conducive to reducing the AC impedance value under high-voltage conditions, and has good anti-drop performance and intermittent cycle performance. There is no sulfur-containing compound in the electrolyte of Comparative Example 1; there is no lithium bis(fluorosulfonyl)imide in the electrolyte of Comparative Example 2; the value of B / A in Comparative Examples 3 to 5 is not within the scope of this application; the change rate of the AC internal resistance of the lithium-ion battery before and after 300 cycles in Comparative Examples 1 to 5 is high, and the pass rate of the drop test and the capacity retention rate of 300 cycles of intermittent cycles at 60°C are low, indicating that the lithium-ion battery of this application is conducive to reducing the AC impedance value under high-voltage conditions, and has good anti-drop performance and intermittent cycle performance.

[0173] The value of A usually affects the AC impedance, anti-drop performance and intermittent cycle performance of the lithium-ion battery under high voltage conditions. It can be seen from Examples 1-4, 1-11 to 1-16 that when the value of A is within the scope of the present application, the rate of change of the AC internal resistance of the lithium-ion battery before and after 300 cycles is low, and the drop test pass rate and the capacity retention rate of 300 intermittent cycles at 60°C are high, indicating that the lithium-ion battery of the present application is conducive to reducing the AC impedance value under high voltage conditions and has good anti-drop performance and intermittent cycle performance.

[0174] The value of B usually affects the AC impedance, anti-drop performance and intermittent cycle performance of the lithium-ion battery under high voltage conditions. It can be seen from Examples 1-1 to 1-10 and 1-26 that when the value of B is within the scope of the present application, the rate of change of the AC internal resistance of the lithium-ion battery before and after 300 cycles is low, and the drop test pass rate and the capacity retention rate of 300 intermittent cycles at 60°C are high, indicating that the lithium-ion battery of the present application is conducive to reducing the AC impedance value under high voltage conditions and has good anti-drop performance and intermittent cycle performance.

[0175] The value of D usually affects the AC impedance, anti-drop performance and intermittent cycle performance of the lithium-ion battery under high voltage conditions. It can be seen from Examples 1-16 to 1-20, 1-27 to 1-28, and 1-38 that when the value of D is within the scope of the present application, the change rate of the AC internal resistance of the lithium-ion battery before and after 300 cycles is low, and the drop test pass rate and the capacity retention rate of 300 intermittent cycles at 60°C are high, indicating that the lithium-ion battery of the present application is beneficial to reducing the AC impedance value under high voltage conditions and has good anti-drop performance and intermittent cycle performance.

[0176] The value of A+D usually affects the AC impedance, anti-drop performance and intermittent cycle performance of the lithium-ion battery under high voltage conditions. It can be seen from Examples 1-11 to 1-20, 1-27 to 1-28, and 1-38 that when the value of A+D is within the scope of the present application, the change rate of the AC internal resistance of the lithium-ion battery before and after 300 cycles is low, and the drop test pass rate and the capacity retention rate of 300 intermittent cycles at 60°C are high, indicating that the lithium-ion battery of the present application is conducive to reducing the AC impedance value under high voltage conditions and has good anti-drop performance and intermittent cycle performance.

[0177] The value of C usually affects the AC impedance, anti-drop performance and intermittent cycle performance of the lithium-ion battery under high voltage conditions. It can be seen from Examples 1-20 to 1-25, 1-29 to 1-30, and 1-39 that when the value of C is within the scope of the present application, the change rate of the AC internal resistance of the lithium-ion battery before and after 300 cycles is low, and the drop test pass rate and the capacity retention rate of 300 intermittent cycles at 60°C are high, indicating that the lithium-ion battery of the present application is conducive to reducing the AC impedance value under high voltage conditions and has good anti-drop performance and intermittent cycle performance.

[0178] The value of A+C usually affects the AC impedance, anti-drop performance and intermittent cycle performance of the lithium-ion battery under high voltage conditions. It can be seen from Examples 1-11 to 1-16, 1-21 to 1-30, and 1-39 that when the value of A+C is within the scope of the present application, the change rate of the AC internal resistance of the lithium-ion battery before and after 300 cycles is low, and the drop test pass rate and the capacity retention rate of 300 intermittent cycles at 60°C are high, indicating that the lithium-ion battery of the present application is conducive to reducing the AC impedance value under high voltage conditions and has good anti-drop performance and intermittent cycle performance.

[0179] The type of sulfur-containing compound usually affects the AC impedance, anti-drop performance and intermittent cycle performance of lithium-ion batteries under high voltage conditions. It can be seen from Examples 1-14 and 1-31 to 1-36 that when the type of sulfur-containing compound is within the scope of the present application, the rate of change of the AC internal resistance of the lithium-ion battery before and after 300 cycles is low, and the drop test pass rate and the capacity retention rate of 300 intermittent cycles at 60°C are high, indicating that the lithium-ion battery of the present application is beneficial to reducing the AC impedance value under high voltage conditions and has good anti-drop performance and intermittent cycle performance.

[0180] Different combinations of electrolytes usually affect the AC impedance, anti-drop performance and intermittent cycle performance of lithium-ion batteries under high voltage conditions. It can be seen from Examples 1-1 to 1-39 that when the combination of electrolytes is within the scope of the present application, the rate of change of the AC internal resistance of the lithium-ion battery before and after 300 cycles is low, and the drop test pass rate and the capacity retention rate of 300 intermittent cycles at 60°C are high, indicating that the lithium-ion battery of the present application is beneficial to reducing the AC impedance value under high voltage conditions and has good anti-drop performance and intermittent cycle performance.

[0181] Table 2

[0182]

[0183]

[0184] The thickness change rate of the positive electrode material layer usually affects the low-temperature cycle performance, high-temperature cycle performance, high-temperature puncture resistance performance, AC impedance under high-voltage conditions, anti-drop performance and intermittent cycle performance of the lithium-ion battery. It can be seen from Examples 1-1 and 2-1 to 2-8 that when the thickness change rate of the positive electrode material layer is within the scope of the present application, the AC internal resistance change rate of the lithium-ion battery before and after 300 cycles is low, and the capacity retention rate of 300 cycles at -20°C, the capacity retention rate of 500 cycles at 45°C, the pass rate of the puncture test at 40°C, the pass rate of the drop test and the capacity retention rate of 300 cycles of intermittent cycles at 60°C are high, indicating that the lithium-ion battery of the present application is beneficial to reducing the AC impedance value under high-voltage conditions, has good anti-drop performance and intermittent cycle performance, as well as good low-temperature cycle performance, high-temperature cycle performance and high-temperature puncture resistance.

[0185] The value of F / T usually affects the low-temperature cycle performance, high-temperature cycle performance, high-temperature puncture resistance performance, AC impedance under high-voltage conditions, anti-drop performance and intermittent cycle performance of the lithium-ion battery. It can be seen from Example 1-1, Example 2-1 to Example 2-10, and Example 2-20 to Example 2-22 that when the value of F / T is within the scope of the present application, the change rate of the AC internal resistance of the lithium-ion battery before and after 300 cycles is low, and the capacity retention rate of 300 cycles at -20°C, the capacity retention rate of 500 cycles at 45°C, the pass rate of the puncture test at 40°C, the pass rate of the drop test and the capacity retention rate of 300 cycles of intermittent cycles at 60°C are high, indicating that the lithium-ion battery of the present application is conducive to reducing the AC impedance value under high-voltage conditions, has good anti-drop performance and intermittent cycle performance, as well as good low-temperature cycle performance, high-temperature cycle performance and high-temperature puncture resistance.

[0186] The mass percentage and type of the first compound usually affect the low-temperature cycle performance, high-temperature cycle performance, high-temperature puncture resistance performance, AC impedance under high-voltage conditions, anti-drop performance and intermittent cycle performance of the lithium-ion battery. It can be seen from Examples 1-1, 2-3, 2-9 to 2-19 that when the mass percentage and type of the first compound are within the scope of the present application, the change rate of the AC internal resistance of the lithium-ion battery before and after 300 cycles is low, and the capacity retention rate of 300 cycles at -20°C, the capacity retention rate of 500 cycles at 45°C, the pass rate of the puncture test at 40°C, the pass rate of the drop test and the capacity retention rate of 300 cycles of intermittent cycles at 60°C are high, indicating that the lithium-ion battery of the present application is conducive to reducing the AC impedance value under high-voltage conditions, has good anti-drop performance and intermittent cycle performance, as well as good low-temperature cycle performance, high-temperature cycle performance and high-temperature puncture resistance.

[0187] Table 3

[0188]

[0189] Note: " / " in Table 3 indicates no relevant preparation parameters. "Lithium phosphate: lithium niobate = 1:2" in Example 3-1 means that the mass ratio of lithium phosphate to lithium niobate is 1:2. The same applies to other examples.

[0190] The coating layer on the surface of the positive electrode material layer usually affects the AC impedance, anti-drop performance and intermittent cycle performance of the lithium-ion battery under high voltage conditions. It can be seen from Example 1-1, Example 3-1 to Example 3-3 that when the parameters of the coating layer on the surface of the positive electrode material layer are within the scope of the present application, the change rate of the AC internal resistance of the lithium-ion battery before and after 300 cycles is low, and the drop test pass rate and the capacity retention rate of 300 intermittent cycles at 60°C are high, indicating that the lithium-ion battery of the present application is beneficial to reducing the AC impedance value under high voltage conditions and has good anti-drop performance and intermittent cycle performance.

[0191] The content of lithium dihydrogen phosphate or aluminum dihydrogen phosphate in the positive electrode material layer usually affects the AC impedance, anti-drop performance and intermittent cycle performance of the lithium-ion battery under high voltage conditions. It can be seen from Examples 1-1, 3-4 to 3-7 that when the value of W is within the scope of the present application, the change rate of the AC internal resistance of the lithium-ion battery before and after 300 cycles is low, and the drop test pass rate and the capacity retention rate of 300 intermittent cycles at 60°C are high, indicating that the lithium-ion battery of the present application is beneficial to reducing the AC impedance value under high voltage conditions and has good anti-drop performance and intermittent cycle performance.

[0192] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.

[0193] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0194] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. An electrolyte comprising lithium bis(fluorosulfonyl)imide, a sulfur-containing compound and propyl propionate, wherein the mass percentage of lithium bis(fluorosulfonyl)imide is A%, the mass percentage of the sulfur-containing compound is B%, 0.3≤B / A≤4, and 0.5≤B≤4 based on the mass of the electrolyte.

2. The electrolyte according to claim 1, wherein 2≤B / A≤3.

5.

3. The electrolyte according to claim 1, wherein 2.5≤B / A≤3.

4. The electrolyte according to claim 1, which satisfies at least one of the following characteristics: (1)0.2≤A≤1.5; (2) Based on the mass of the electrolyte, the mass percentage of the propyl propionate is D%, 30≤D≤40.

5. The electrolyte according to claim 1, wherein 30.5≤A+D≤41.

6. The electrolyte according to claim 1, wherein The sulfur-containing compounds include 1,3-propane sultone, 1-fluoro-1,3-propane sultone, 2-fluoro-1,3-propane sultone, 3-fluoro-1,3-propane sultone, 1-methyl-1,3-propane sultone, 2-methyl-1,3-propane sultone, 3-methyl-1,3-propane sultone, 1-propylene-1,3-sultone, 2-propylene-1,3-sultone, 1-fluoro-1-propylene-1,3-sultone, 2-fluoro-1-propylene-1,3-sultone, 3-fluoro-1-propylene-1,3-sultone, 1-fluoro-2-propylene-1,3-sultone At least one of ester, 2-fluoro-2-propylene-1,3-sultone, 1-methyl-1-propylene-1,3-sultone, 2-methyl-1-propylene-1,3-sultone, 3-methyl-1-propylene-1,3-sultone, 1-methyl-2-propylene-1,3-sultone, 2-methyl-2-propylene-1,3-sultone, 3-methyl-2-propylene-1,3-sultone, 1,4-butanesultone, 1,5-pentanesultone, methylene methanedisulfonate, ethylene methanedisulfonate, sulfolane, methyl sulfolane, 4,5-dimethyl sulfolane or sulfolene.

7. The electrolyte according to claim 1, wherein The sulfur-containing compound includes at least one of 1,3-propane sultone or sulfolane.

8. The electrolyte according to claim 1, wherein The electrolyte further comprises 3-bromo-5-chloro-1-phenylthiophene. Based on the mass of the electrolyte, the mass percentage of 3-bromo-5-chloro-1-phenylthiophene is C%, and 1.8≤C≤3.

8.

9. The electrolyte according to claim 8, wherein 2≤A+C≤4.

8. 10 . An electrochemical device comprising a positive electrode sheet, a negative electrode sheet, a separator and the electrolyte according to claim 1 .

11. The electrochemical device according to claim 10, wherein: The positive electrode plate includes a positive electrode material layer, which includes amorphous carbon; a ball with a diameter of 15 mm and a weight of 12 g falls on the positive electrode material layer from a height of 0.1 m to 0.5 m, and the thickness change rate of the positive electrode material layer is 1% to 20%.

12. The electrochemical device according to claim 11, wherein The positive electrode material layer includes a first compound, which includes at least one of polybutyl acrylate, polyethyl acrylate, polybutyl methacrylate or polymethyl methacrylate. Based on the mass of the positive electrode material layer, the mass percentage of the first compound is 0.01% to 0.28%.

13. The electrochemical device according to claim 10, wherein: At 160° C., the thermal shrinkage rate of the separator in the width direction after the separator is unfolded is F%, and the thickness of the positive electrode sheet is T μm, and 0.04≤F / T≤0.

1.

14. An electronic device comprising the electrochemical device according to any one of claims 10 to 13.